Biogeochemical Argo: The Test Case of the NAOS Mediterranean Array - D’Ortenzio, Fabrizio; Taillandier, Vincent; Claustre, Hervé; Prieur, Louis Marie; Leymarie, Edouard; Mignot, Alexandre; Poteau, Antoine; Penkerc’h, Christophe; Schmechtig, Catherine Marie (Frontiers in Marine Science, 2020)
The necessity of wide, global-scale observing systems for marine biogeochemistry emerged dramatically in the last decade. A global network based on Biogeochemical (BGC) Argo floats is considered as one of the most promising approaches for reaching this goal. As a first step, pilot studies were encouraged to test the feasibility of a global BGC-Argo array, to consolidate the methods and practices under development, and to set up the array’s characteristics. A pilot study in the Mediterranean Sea—deemed a suitable candidate for a test case because it combines a relatively large diversity of oceanic biogeochemical conditions in a reduced open-ocean basin—was consequently approved as a part of the NAOS (“Novel Argo ocean Observing System”) project, a French national initiative to promote, consolidate and develop the Argo network. We present here a first assessment of the NAOS Mediterranean array, in view of scientific choices on observing-system strategy, on implementation and statistics on network performances, and on data-quality control.